The Physicochemical and Microbiological Quality of Pegagan Duck Eggs Immersed with Duku Fruit Peel Solution in Different Storage Period - Fitra Yosi; Dyah Wahyuni; Riswandi .; Fitri Herasti; Inda Ayu Lestari; Makinudin . (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This study aims to determine the effect of immersing in duku fruit peel solution on physicochemical and microbiological quality of Pegagan duck eggs during storage at room temperature. This study used a complete randomized design (CRD) with a 5x3 factorial patterned. The first factor was the immersion time consisting of 5 levels, namely 0, 15, 30, 45, and 60 min. The second factor was the storage time which includes 3 levels, which were 0, 7 and 14 d. The replication used was 3 times. The observed variables were physicochemical and microbiological quality of egg, including albumen index (AI), yolk index (YI), Haugh unit (HU), moisture content (MC), protein content (PC), fat content (FC),total microbes (TM) and antioxidant activity (AA). The data were processed by analysis of variance, continued with Duncan's multiple range test (DMRT). The results showed that there was a significant interaction (P<0.05) between immersion time and storage time on AI, YI, HU, MC, PC, TM, and AA. Futhermore, the difference of immersion time and storage period was also significantly influenced (P<0.05) to all observed variables including AI, YI, HU, MC, PC, TM, and AA of duck eggs.It can be concluded that the immersion process for 60 min showed the best results on the physical, chemical,